The Mediation Role of OCB on the Effect of the Big Five Personality on Nurse Performance - Anton Prasetyo (Jurnal Manajemen dan Organisasi, 2022)
OCB behavior has an important role in organizational effectiveness because OCB can improve organizational performance. The purpose of this study is to determine and examine the effect of the big five personalities on job performance with OCB as a mediating variable for nurses at RSUD dr. Soedirman, Kebumen. The sample in this study are 155 nurses. The analysis in this study uses the Partial Least Square Structural Equation Model (PLS-SEM) analysis. The results of the analysis show that the dimensions of the big five personalities, namely extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience have a positive and significant effect on OCB; the dimensions of extraversion, conscientiousness, and openness to experience have a positive and significant effect on job performance, while the dimensions of agreeableness and neuroticism do not affect job performance; OCB has a positive and significant effect on job performance; and OCB is able to mediate the effect of agreeableness, conscientiousness, and openness to experience on job performance, and OCB can not mediate the effect of extraversion and neuroticism on job performance.